SMALL DOESN'T MEAN CAN'T SURVIVE : MICRO SMALL AND MEDIUM FAMILY BUSINESS SUCCESSION STRATEGY - chusnul rofiah (Faculty of Business, President University, 2022)
Many family-owned companies at the micro, small and medium level have failed to plan for succession in business (Voithofer & Mandl, 2004). It is very different from family business continuity succession planning in large companies compared to micro, small and medium businesses even though the business is unique and creative. In large companies, the selection of successors is much wider than that of family owned micro, small and medium enterprises because candidates in family business are only for family members (Tatoglu et al., 2008). reveals a family business succession planning strategy with a phenomenological approach. The findings of this study provide a valuable understanding of family business in the selected factors: (1) The importance of the level of heir preparation and the relationship between family and business members on business performance, (2) Family business becomes a strategy for growth, increasing competitiveness in the business world , (3) Successor skills are the most important factor in successor selection and positive effect on family business performance, (4) Successors are asked to join the family business, (5) Founders and predecessors, build self-confidence, promote positive attitudes and facilitate the transition process, (6) Succession planning, consistency in high-quality communication is required for adequate business exploration and addressing all issues. Based on this research, family companies emphasize the awareness of the importance of succession planning in their business, especially in relation to performance, efficiency and sustainability. This phenomenon will help increase income, productivity and help MSMEs, in terms of finance, and facilitate the regeneration of family businesses.